Plans for Early 20th-Century Toronto: Lost in Management - Lemon, James (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1989)
On several occasions in the early twentieth century, advocates of urban planning proposed significant measures for altering the layout of Toronto streets. Planning historians often have proposed that an interest in beautification was superseded by a focus on efficiency by the 1920s, but Toronto's plans largely were lost amidst private development processes and business cycles. Confusion over planning priorities, the short-term perspectives of politicians, and a lack of urgency also impeded city and regional planning. Toronto experienced less planning initiatives than major United-States cities.